Pengaruh Koordinasi Kerja, Motivasi Kerja, dan Organizational Citizenship Behavior terhadap Kinerja Pegawai Negeri: (Studi Pada Badan Kesatuan Bangsa Dan Politik (KESBANGPOL), Kota Denpasar) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study focuses on "The Influence of Work Coordination, Work Motivation, and Organizational Citizenship Behavior on Employee Performance at the National Unity and Political Agency (Kesbangpol), Denpasar City". There are often conflicting meeting schedules so that you have to reschedule the meeting agenda, being late in preparing a file so that the administrative process is hampered, this also affects the accumulation of work because previous work has not been completed, the division of work that is not in accordance with the field makes a lack of mastery of work, so make employees who are asked for help feel compelled to help so that team goals are still achieved. Data collection methods in this study were documentation, literature study, interviews, observation and questionnaires. Data analysis techniques used by researchers are validity test, reliability test, classical assumption test and multiple linear regression analysis. The results showed that work coordination, motivation, and Organizational Citizenship Behavior had a positive and significant effect on the performance of employees at Kesbangpol Denpasar City. Efforts are needed to strengthen these factors together in order to create a productive and efficient work environment to optimally support the achievement of organizational goals.